The Influence of Price and Co-Branding on Purchase Decisions of Azarine Products with Consumer Satisfaction as a Mediating Variable at Underprice Skincare Stores in Medan - Pane, Sari Aparpan; Hutasuhut, Saidun (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to examine the influence of price and co-branding on purchase decisions of Azarine products, with customer satisfaction acting as a mediating variable between price and purchase decision. The research method used is a quantitative approach by distributing questionnaires to consumers who have purchased Azarine products and Azarine co-branded products at Underprice Skincare Store Medan. The data analysis technique used in this study is SEM-PLS to test the relationship between variables. The results show that price, co-branding, and customer satisfaction have a positive and significant influence on purchase decisions. Furthermore, customer satisfaction is proven to mediate the relationship between price and purchase decisions of Azarine products at Underprice Skincare Store Medan. These findings indicate that while affordable pricing is an important factor in consumer decision-making, an effective co-branding strategy and high customer satisfaction can serve as key drivers in encouraging purchase decisions.